N6-methyladenosine-modification of USP15 regulates chemotherapy resistance by inhibiting LGALS3 ubiquitin-mediated degradation via AKT/mTOR signaling activation pathway in hepatocellular carcinoma - Ronghuan Fang; Zhigang Jia; Yuhang Xin; Kai Zhao; Wei Qin; Haoran Lu; Yi Zhou; Yongsheng Yang; He Fang (Cell Death Discovery)
Abstract Hepatocellular carcinoma (HCC) is among the most malignant tumors and seriously threatens human health worldwide, and its incidence rate is increasing annually. USP15 is a member of the ubiquitination-specific protease (USP) family, which can regulate protein ubiquitination, thereby affecting their stability, and is dysregulated in many cancers, but its expression and regulatory mechanism in HCC are unclear. The aims of this study were to explore the role and mechanism of USP15 in regulating HCC cell stemness, proliferation, and lenvatinib resistance. Immunohistochemistry and high-throughput sequencing analyses of tumor and adjacent normal tissue samples from 52 patients with HCC were conducted. Functional analyses of immortalized human liver and HCC cell lines were conducted, including quantitative real-time PCR; western blot; plasmid, lentivirus, and siRNA transfection; co-immunoprecipitation; mass spectrometry; MeRIP-qPCR; and ubiquitination, cell growth, colony formation, and spheroid formation assays. HCC tumor growth was also assessed using cell transplantation in nude mice. We found that USP15 is upregulated in HCC and affects patient prognosis. Our results demonstrated that USP15 can increase LGALS3 stability in HCC through deubiquitination modification, and affect the stemness, proliferation, and lenvatinib resistance of HCC cells by activating the AKT/mTOR pathway. USP15 expression levels were positively correlated with HCC cell stemness, proliferation, and lenvatinib resistance. In addition, methyltransferase-like protein 3 (Mettl3) N6-methyladenosine (m6A) modified USP15 to upregulate its levels by increasing its mRNA stability. These findings provide a theoretical basis for the potential discovery of new HCC oncogenes, as well as the identification of effective targets and development of novel anti-HCC drugs and clinical applications.